Clinical peculiarities of Lyme carditis in patients of different age and gender - K.V. Myndziv; N.I. Yarema (Вісник медичних і біологічних досліджень, 2022)
Summary. Lyme disease is the most common infectious transmissible disease in the countries of the Northern Hemisphere, caused by the spirochetes Borrelia burgdorferi sensu lato (Bbsl), which are carried by Ixodes ticks. The incidence rate of Lyme borreliosis increased more than 52 times from 2005 to 2019, according to the Center for Public Health of the Ministry of Health of Ukraine. The aim of the study – to analyze the clinical course of Lyme carditis (LC) in adult patients of different age and gender who were hospitalized in the cardiology department of the CNE "Ternopil Regional Clinical Hospital" TRC. Materials and Methods. 33 patients with LC, aged from 18 to 65 years, were examined. All patients underwent traditional clinical and laboratory tests in the conditions of the clinical laboratory of CNE “TRCH” TRC in accordance with the recommendations for patients with myocarditis of the Association of Cardiologists of Ukraine (2014), as well as the recommendations of the European Association of Cardiology (ESC), 2020. The etiological factor of LC was determined with enzyme immunoassay method blood serum analysis of specific antibodies to B.burgdorferi s.l. class IgM and IgG, and also blot analysis was used. Statistical processing of the research results was carried out using the created database of examined patients in the StatSoft Statistica v 10.0 program. Results. The average age of the patients was (45.0±2.4) years. 27.3 % of examined patients noted tick bites. Significantly higher levels of erythrocyte sedimentation rate, C-reactive protein, creatine phosphokinase-MB, troponin T and NT-pro BNP were determined in patients with a severe course of Lyme carditis compared to a moderately severe course and both groups of patients compared to the control group, which indicates a significant role of the inflammatory component in the process of damage to the heart muscle and, as a result, in the development of heart failure. Conclusions. LC mostly affected young men. It was established that the activity of the inflammatory process intensifies with increasing severity of the course of the disease. AV-blockades (45.6 %) and LBBB (33.3 %) were the most frequent in the examined patients with LC. 48.5 % of patients with LC were diagnosed with II FC NYHA, and 51.5 – III FC NYHA. The severity of the course of LC was due to the increase in heart failure